1993
DOI: 10.1073/pnas.90.18.8494
|View full text |Cite
|
Sign up to set email alerts
|

Polyoma virus early-late switch: regulation of late RNA accumulation by DNA replication.

Abstract: Early in infection of permissive mouse cells, messages from the early region of the polyoma virus genome accumulate preferentially over those from the late region. After initiation of DNA replication, the balance between early and late gene expression is reversed in favor of the late products. In previous work from our laboratory, we showed that viral early proteins do not activate the polyoma late promoter in the absence ofDNA replication. Here The molecular details underlying the early-late switch are poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 38 publications
0
44
0
1
Order By: Relevance
“…We, and others, have reported that the early-to-late switch is characterized by a change in the efficiency of usage of the viral late polyadenylation signal. At early times, polyadenylation and transcription termination are efficient on the late strand; these transcripts are relatively unstable in the nucleus and accumulate to only low levels Carmichael 1988, 1990;Liu and Carmichael 1993;Liu et al 1994). At late times, however, polyadenylation and transcription termination become inefficient, leading to multigenomic primary transcripts (Acheson et al 1971;Acheson 1976Acheson , 1978Birg et al 1977;Treisman 1980;Treisman and Kamen 1981).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We, and others, have reported that the early-to-late switch is characterized by a change in the efficiency of usage of the viral late polyadenylation signal. At early times, polyadenylation and transcription termination are efficient on the late strand; these transcripts are relatively unstable in the nucleus and accumulate to only low levels Carmichael 1988, 1990;Liu and Carmichael 1993;Liu et al 1994). At late times, however, polyadenylation and transcription termination become inefficient, leading to multigenomic primary transcripts (Acheson et al 1971;Acheson 1976Acheson , 1978Birg et al 1977;Treisman 1980;Treisman and Kamen 1981).…”
Section: Resultsmentioning
confidence: 99%
“…Late pre-mRNAs contain tandem copies of the noncoding late leader exon. These exons are efficiently spliced to one another, leading to the further stabilization and processing of late mRNAs Carmichael 1988, 1990;Liu and Carmichael 1993). (Bottom) RT-PCR can be used to reveal leader-to-leader splicing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon differentiation in suprabasal cells, viral DNA amplification is activated, along with late transcription, leading to virion production (23). A link between productive viral replication and late gene expression has been well documented in other DNA tumor viruses such as simian virus 40 (SV40) (53,54), polyomavirus (8,9,27,31), and adenoviruses (51), but it is not clear if this extends to papillomaviruses.…”
mentioning
confidence: 99%